PENGEMBANGAN MULTIMEDIA PEMBELAJARAN SD PADA MATERI KEBERAGAMAN SUKU BANGSA TEMA 7 KELAS IV SEKOLAH DASAR - Dini, Rahma; Nuristia Asih, Nofi; Harjanto, Ambyah (Pedagogia: Jurnal Ilmiah Pendidikan Dasar Indonesia, 2020)
Based on the initial research conducted, the researcher found the problem that the teacher was not maximal in using learning media, so this study aims to determine the development of interactive learning media that utilizes a technological development in the form of multimedia. To find out the feasibility of the media, and to find out the effectiveness of the interactive learning media based on the material on the diversity of ethnic groups in the theme of 7 grade IV elementary schools. utilizing a technological development in the form of multimedia Product design, making this learning media utilizes network-based digital technology by using a video maker application to combine various images that contain learning material, the selected images are also images that suit students, namely in the form of animated image. Where an interesting animation creates a sense of interest for the students themselves. The results of this study obtained an expert assessment of the media developed by researchers, namely interactive learning media that utilizes a technological development in the form of multimedia to obtain appropriate and very feasible criteria for differences in the results of social studies material on ethnic diversity theme 7 class IV before and after using interactive learning media a technological development in the form of multimedia. The conclusion of this study is that this interactive learning media gives students the success of learning through the media of a video accompanied by written learning material as an explanation for students and also uses a sound background so that students who watch are more interested and find learning more enjoyable. In addition, schools are also advised to facilitate educators to participate in media development training in order to broaden their horizons.